2009
DOI: 10.1021/om9000764
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Coordination Chemistry of a Tridentate o-Phenylene-Bridged Diphosphine−NHC System

Abstract: The preparation of a di-o-phenylene-bridged tridentate PCP donor set is described starting with t-BOCaniline followed by a series of steps that include lithiation, quenching with Pr i 2 PCl, conversion to the phosphine sulfide, and assembling the unsaturated N-heterocyclic carbene unit. After desulfurization, the imidazolinium unit flanked by two phosphine units, represented as [(PCP)H]PF 6 is obtained. Subsequent reaction with group 10 M(0) reagents (Ni(COD) 2 , Pd(PPh 3 ) 4 , and Pt(PPh 3 ) 4 ) generates goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 50 publications
8
57
1
1
Order By: Relevance
“…The classical trialkylorthoformate route followed by reduction of the sulfides led to the bis-(phosphine) imidazolinium salt 33. 60 Gautier and co-workers recently showed that the "classical" SIMes imidazolinium salt could be obtained in 53% overall yield by using this alkylating route. Reaction of mesitylamine with 1,2-dibromoethane was efficiently conducted in methanol as solvent.…”
Section: Trialkyl Orthoformate (Hc(or) 3 ) As the Precarbenic Unitmentioning
confidence: 99%
“…The classical trialkylorthoformate route followed by reduction of the sulfides led to the bis-(phosphine) imidazolinium salt 33. 60 Gautier and co-workers recently showed that the "classical" SIMes imidazolinium salt could be obtained in 53% overall yield by using this alkylating route. Reaction of mesitylamine with 1,2-dibromoethane was efficiently conducted in methanol as solvent.…”
Section: Trialkyl Orthoformate (Hc(or) 3 ) As the Precarbenic Unitmentioning
confidence: 99%
“…There is an isolated report of the use of the oxidation method (Scheme 15) reported for the preparation of the (772) [237] from the reaction of the imidazolinium salt and Ni(COD) 2 .…”
Section: Mono-cationic Chelated Ni(ii)−nhc Complexesmentioning
confidence: 99%
“…These ligands range from the ubiquitous 2,2',6',2''-terpyridine [23] (tpy, 6 in Figure 2) to bis-(imino)pyridine systems 7, studied for late-transition-metal alkene polymerizations, [24] and related pyridine-based scaffolds such as 8 [25] and 9. [26] Other neutral tridentate frameworks, including structures 10 [27] and 11, [28] have also recently been developed, but little emphasis has so far been placed on catalytic applicability of these systems.…”
Section: Introductionmentioning
confidence: 99%